Molecular dynamical simulations of melting Al nanoparticles using a reaxff reactive force field. (6th June 2018) - Liu, Junpeng; Wang, Mengjun; Liu, Pingan
Abstract: Molecular dynamics simulations were performed to study thermal properties and melting points of Al nanoparticles by using a reactive force field under canonical (NVT) ensembles. Al nanoparticles (particle size 2–4 nm) were considered in simulations. A combination of structural and thermodynamic parameters such as the Lindemann index, heat capacities, potential energy and radial-distribution functions was employed to decide melting points. We used annealing technique to obtain the initial Al nanoparticle model. Comparison was made between ReaxFF results and other simulation results. We found that ReaxFF force field is reasonable to describe Al cluster melting behavior. The linear relationship between particle size and melting points was found. After validating the ReaxFF force field, more attention was paid on thermal properties of Al nanoparticles with different defect concentrations. 4 nm Al nanoparticles with different defect concentrations (5%–20%) were considered in this paper. Our results revealed that: the melting points are irrelevant with defect concentration at a certain particle size. The extra storage energy of Al nanoparticles is proportional to nanoparticles' defect concentration, when defect concentration is 5%–15%. While the particle with 20% defect concentration is similar to the cluster with 10% defect concentration. After melting, the extra energy of all nanoparticles decreases sharply, and the extra storage energy is nearly zero at 600 K. The centro-symmetry parameter analysis shows structure evolution of different models during melting processes.